Silver nanoparticle incorporation on polyamide 6,6 fabrics by hybrid corona-dielectric barrier discharge for antimicrobial applications - Francelino, Isabella Grinberg; Tavares, Victória Kelly Fonseca [UNESP]; Leite, Lady Daiane Pereira [UNESP]; da Silva, Diego Morais [UNESP]; de Souza Miranda, Felipe [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Filho, Gilberto Petraconi (Springer Nature, 2025)
Silver nanoparticles (AgNPs) have been extensively studied due to their antimicrobial properties against several pathogenic microorganisms. A particularly promising application of these nanoparticles involves their incorporation into textiles to enhance the efficacy of face masks. This work aims to deposit AgNPs on polyamide 6,6 fabrics using a hybrid corona-dielectric barrier discharge plasma reactor and evaluate their antimicrobial effect as well as their cytotoxicity. Prior to deposition, the fabrics were activated in air plasma at atmospheric pressure. The deposition process was then initiated by nebulizing a silver nanoactive into the system by a flat cavity present in the high-voltage electrode, a distinctive feature that sets this approach apart from other AgNP deposition techniques reported in the literature. The incorporation of AgNPs on polyamide 6,6 fabric surface was confirmed by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The thermal behavior of the samples was studied by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). To identify the crystalline phases, X-ray diffraction (XRD) analyses were performed on control (without AgNPs) and treated (with AgNPs) samples. Microbiological analysis was based on the AATCC 100–2019 test method with modifications for two different species of bacteria: Staphylococcus aureus and Klebsiella pneumoniae. Bacterial suspensions with 1–3 × 105 cells/mL were inoculated into control and treated samples, followed by viable cell count (CFU/mL). Statistically significant reductions in bacterial counts were detected, with 62.37% and 74.63% reduction percentages compared to the control sample for Staphylococcus aureus and Klebsiella pneumoniae, respectively. Furthermore, cytotoxicity analysis, performed according to ISO 10993–5/2009, showed that the treated fabrics are not cytotoxic due to higher viability than 70%.
Keywords: Antimicrobial effect; Corona-dielectric barrier discharge; Cytotoxicity; Polyamide 6,6; Silver nanoparticles